2014
DOI: 10.1016/j.jconrel.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Pollen grains for oral vaccination

Abstract: Oral vaccination can offer a painless and convenient method of vaccination. Furthermore, in addition to systemic immunity it has potential to stimulate mucosal immunity through antigen-processing by the gut-associated lymphoid tissues. In this study we propose the concept that pollen grains can be engineered for use as a simple modular system for oral vaccination. We demonstrate feasibility of this concept by using spores of Lycopodium clavatum (clubmoss) (LSs). We show that LSs can be chemically cleaned to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
147
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(162 citation statements)
references
References 45 publications
(48 reference statements)
11
147
1
Order By: Relevance
“…[30][31][32] Most conventional techniques used for encapsulation such as emulsion solvent evaporation, spray drying, and chemical conjugation fail to reliably provide either size monodispersity or well-defi ned microstructures. [ 26,27,[30][31][32] Although several studies have reported the use of empty exine microcapsules for the encapsulation of drugs, vaccines, and magnetic resonance imaging (MRI) contrast agents, as well as for use in cosmetics and food supplements, [ 7,[16][17][18]22 ] the use of the natural "spores" as a microencapsulation material and delivery vehicle still remains unexplored. In this regard, we have directed our efforts toward exploring systems to produce macromoleculeloaded spores using three different microencapsulation techniques.…”
Section: Doi: 101002/adfm201502322mentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Most conventional techniques used for encapsulation such as emulsion solvent evaporation, spray drying, and chemical conjugation fail to reliably provide either size monodispersity or well-defi ned microstructures. [ 26,27,[30][31][32] Although several studies have reported the use of empty exine microcapsules for the encapsulation of drugs, vaccines, and magnetic resonance imaging (MRI) contrast agents, as well as for use in cosmetics and food supplements, [ 7,[16][17][18]22 ] the use of the natural "spores" as a microencapsulation material and delivery vehicle still remains unexplored. In this regard, we have directed our efforts toward exploring systems to produce macromoleculeloaded spores using three different microencapsulation techniques.…”
Section: Doi: 101002/adfm201502322mentioning
confidence: 99%
“…[ 1 ] L. clavatum spores are used in traditional herbal medicine and have been shown to exhibit a wide range of therapeutic benefi ts including improved osteogenesis, [ 11 ] improved cognitive function, [ 12 ] treatment of gastrointestinal disorders, [ 8 ] hepatoprotective activity, [ 13 ] and antioxidative properties. [ 14 ] Recent studies have demonstrated the use of processed L. clavatum shells for encapsulation, [15][16][17][18][19] however, the production of L. clavatum sporopollenin capsules requires the prolonged processing of natural spores with harsh chemical treatments at elevated temperatures, so as to isolate the sporopollenin exine shell. [20][21][22][23][24] In many applications, this extensive processing may be unnecessary and potential therapeutic benefi ts may be lost.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their complex biologically derived morphology, these mimics may provide unique function as fillers. In addition, pollen exine has been proposed as vehicles for the delivery of pharmaceuticals and vaccines [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Applications as microcapsules: the capability of exines from L. clavatum to act as microcapsules (Figure 1) was demonstrated ) for a range of polar and non-polar materials, over a wide range of molecular weights, from water to proteins up to 2000 kDa (Atwe et al, 2014). Notably, neither the sporopollenin nor the encapsulation procedure was significantly deleterious to the enzymes' activity, thus offering the possibility of the exines to act as micro-reaction vessels or transporters of enzymes.…”
mentioning
confidence: 99%
“…The mechanism involved may be associated with bioadhesion of the exine capsules in the gastrointestinal tract. A later in vivo study in mouse showed that the sporopollenin exines filled with ovalbumin as a model antigen could be used for oral immunization and which demonstrates the potential of the exines to be used for oral vaccination (Atwe et al, 2014). The authors offered evidence by confocal microscopy that the exines translocate across the mouse intestinal epithelium, which, the authors proposed, might be involved in the stimulation of the immune system.…”
mentioning
confidence: 99%